2018
DOI: 10.7150/thno.21463
|View full text |Cite
|
Sign up to set email alerts
|

AKR1C1 Activates STAT3 to Promote the Metastasis of Non-Small Cell Lung Cancer

Abstract: Metastasis is the leading cause of mortality for human non-small cell lung cancer (NSCLC). However, it is difficult to target tumor metastasis because the molecular mechanisms underlying NSCLC invasion and migration remain unclear. Methods: GEO data analyses and IHC analyses were performed to identify that the expression level of AKR1C1, a member of human aldo-keto reductase family, was highly elevated in patients with metastasis or metastatic foci of NSCLC patients. Functional analyses (in vitro and in vivo) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 53 publications
(60 reference statements)
1
61
0
Order By: Relevance
“…Besides, AKR1C1/2/3 jointly acting as significant risk factors on prognosis was also validated in HCC patients. High expression of AKR1C1 was observed in many solid tumors and increasing studies have used AKR1C1 as a therapeutic target for treatment of cancers [3,23]. Our study firstly showed that AKR1C1 was also high-expressed in HCC tissues and high mRNA expression of AKR1C1 predicted poor OS and PFS.…”
Section: Discussionmentioning
confidence: 55%
“…Besides, AKR1C1/2/3 jointly acting as significant risk factors on prognosis was also validated in HCC patients. High expression of AKR1C1 was observed in many solid tumors and increasing studies have used AKR1C1 as a therapeutic target for treatment of cancers [3,23]. Our study firstly showed that AKR1C1 was also high-expressed in HCC tissues and high mRNA expression of AKR1C1 predicted poor OS and PFS.…”
Section: Discussionmentioning
confidence: 55%
“…Our RNA-Seq data suggested that some EMT-related genes (AKR1C1, CDH11, PCDH8, and CXCR2) were differentially expressed due to CHODL in CRC. AKR1C1, a member of the human aldo-keto reductase family, was downregulated according to our RNA-Seq analysis, and it exerts its prometastatic effects by directly interacting with STAT3, facilitating its phosphorylation and reinforcing STAT3 binding to the promoter regions of JAK2, which might promote metastasis in a catalytic-independent manner [29]. CDH11 is a mesenchymal cadherin that promotes cell migration by enhancing TGFβ-stimulated signaling [30].…”
Section: Discussionmentioning
confidence: 94%
“…These data implied that AKR1C1 was not a driver factor in the process of carcinogenesis and progression in NPC, AKR1C1 loss maybe an accompanying molecular event which contributed only to the chemotherapeutic sensitivity to cisplatin while not the malignant biological behaviours of NPC. Although AKR1C1 is reported to be involved in tumour metastasis through interaction with STAT3 in NSCLC 27 and to promote invasion of bladder cancer cells, evidence supporting the facilitation of metastasis is still lacking 17 . Taken together, the functional explorations of AKR1C1 provided a reasonable answer for the contradictory phenomenon between the expression data and the prognostic data in NPC.…”
Section: Discussionmentioning
confidence: 99%